2014
DOI: 10.1007/s11524-014-9876-5
|View full text |Cite|
|
Sign up to set email alerts
|

Modeling Minority Stress Effects on Homelessness and Health Disparities among Young Men Who Have Sex with Men

Abstract: Sexual minority youth are more likely to experience homelessness, and homeless sexual minority youth report greater risk for mental health and substance abuse symptoms than homeless heterosexual youth, yet few studies have assessed determinants that help explain the disparities. Minority stress theory proposes that physical and mental health disparities among sexual minority populations may be explained by the stress produced by living in heterosexist social environments characterized by stigma and discriminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 49 publications
2
34
0
1
Order By: Relevance
“…In contrast, school enrollment was associated with less drug use among Black SMY [68]. Compared to Whites, racial/ethnic minority adolescent SMY also reported disproportionately high rates of stigma [92], physical threats/victimization, and feeling unsafe at school [28]. Each of these was associated with greater risk of substance use [78, 58, 24, 36, 39].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, school enrollment was associated with less drug use among Black SMY [68]. Compared to Whites, racial/ethnic minority adolescent SMY also reported disproportionately high rates of stigma [92], physical threats/victimization, and feeling unsafe at school [28]. Each of these was associated with greater risk of substance use [78, 58, 24, 36, 39].…”
Section: Resultsmentioning
confidence: 99%
“…11,12,14 It is possible that the paths to homelessness for an older population of sexual and gender minorities are more similar to those for older heterosexual and cisgender individuals, or that if they differ, these differences were not captured in our measures of reasons for becoming homeless.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, estimates have suggested that sexual and gender minorities comprise between 22.4 and 40 % of homeless youth. 9,10 Reasons for this increased risk of homelessness can include family conflict, 11 disapproval of sexual orientation, 12,13 or stressful experiences such as childhood sexual abuse. 14 The reason that sexual minority individuals become homeless may in turn be related to their experiences later on, for example, young sexual minority men who were kicked out of their homes were more likely to have daily marijuana use or to have experienced recent homelessness.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MSM demonstrate high prevalence and severity of mental health disorders and substance use disorders relative to their heterosexual male counterparts [10,11], and samples of homeless MSM demonstrate greater prevalence of substance use and mental health disorders relative to their unstably housed heterosexual counterparts [12-14]. …”
Section: Introductionmentioning
confidence: 99%